Perlindungan Hukum terhadap Anak Korban Cyberbullying Ditinjau dari Undang-Undang Perlindungan Anak - Defri Sembiring (Jurnal Hukum Lex Generalis, 2026)
The increasing use of information technology in the digital era has had an impact and influence on the increase in cases of cyberbullying, which places minors as the most vulnerable group. This study aims to analyze the form of legal protection for children who are victims of cyberbullying, as well as to examine the provisions of criminal sanctions against perpetrators of these crimes based on laws and regulations in Indonesia. The research method used is normative juridical with a statute approach and a case approach. The focal point of the study is directed at Law Number 17 of 2016 concerning the Stipulation of Government Regulation in Lieu of Law Number 1 of 2016 concerning the Second Amendment to Law Number 23 of 2002 concerning Child Protection to Become Law. The results of this study indicate that this law provides legal protection in the form of preventive and repressive efforts, as well as the right to restitution and rehabilitation to restore the psychological condition of children who are victims. Regarding criminal sanctions, acts of psychological violence in the form of bullying can be prosecuted through Article 76C jo. Article 80 of the law, in addition to the imposition of articles in the Electronic Information and Transactions Law (UU ITE), does not specifically define the nomenclature of cyberbullying. Therefore, legal reform and changes are recommended by inserting or adding a specific article regarding cybercrimes based on child bullying and strengthening criminal sanctions to provide a comprehensive deterrent effect, as well as requiring social media platform providers to restrict access for underage users.